The kinetic study of the methane oxidation reaction catalyzed by transition metal oxides RuO/RhO/PdO. Issue 5 (23rd March 2020) - Liu, Hongxia; Fu, Ling; He, Chaozheng
ABSTRACT: The relative stability and kinetics of CH4 … O2 … MO and the reaction potential energy surface under the transition metal oxide catalysts (RuO/RhO/PdO) during methane oxidation reaction were studied with density functional calculations. The results show that the reaction can be easily carried out under the catalysis of transition metal oxides. The transition barriers and the reaction rate constant all show oscillation modes that are consistent with the increase of atomic number at 298 K. while the calculated reaction energies ( E r/kcal mol− 1 ) are gradually increased. The oxidised dioxide can be treated to form metal and oxygen that can still be used as a catalyst for methane oxidation; the resulting oxygen can continue to be used as an oxidant. We also calculated the rate constant of methane oxidation reaction to give the resulting methanol pathway. The calculated dynamic characterisation shows that the rate constant has a positive temperature dependence. Our calculation show that this reaction is exothermic reaction via the RuO/RhO/PdO catalyst, and the reaction is thermodynamically feasible. This study also provides theoretical reference data for us to identify new catalysts for the catalytic oxidation of methane.